Electronic Modulation of Metal–Organic Frameworks by Interfacial Bridging for Efficient pH‐Universal Hydrogen Evolution. (26th October 2022) - Wang, Luqi; Song, Li; Yang, Zhenyu; Chang, Yu‐Ming; Hu, Feng; Li, Lei; Li, Linlin; Chen, Han‐Yi; Peng, Shengjie
Abstract: Designing well‐defined interfacial chemical bond bridges is an effective strategy to optimize the catalytic activity of metal–organic frameworks (MOFs), but it remains challenging. Herein, a facile in situ growth strategy is reported for the synthesis of tightly connected 2D/2D heterostructures by coupling MXene with CoBDC nanosheets. The multifunctional MXene nanosheets with high conductivity and ideal hydrophilicity as bridging carriers can ensure structural stability and sufficient exposure to active sites. Moreover, the Co–O–Ti bond bridging formed at the interface effectively triggers the charge transfer and modulates the electronic structure of the Co‐active site, which enhances the reaction kinetics. As a result, the optimized CoBDC/MXene exhibits superior hydrogen evolution reaction (HER) activity with low overpotentials of 29, 41, and 76 mV at 10 mA cm −2 in alkaline, acidic, and neutral electrolytes, respectively, which is comparable to commercial Pt/C. Theoretical calculation demonstrates that the interfacial bridging‐induced electron redistribution optimizes the free energy of water dissociation and hydrogen adsorption, resulting in improved hydrogen evolution. This study not only provides a novel electrocatalyst for efficient HER at all pH conditions but also opens up a new avenue for designing highly active catalytic systems. Abstract : A novel CoBDC/MXene electrocatalyst with 2D/2D heterostructure is prepared by a facile in situ growth strategy, in which the formation of interfacial Co–O–Ti bridges effectively tunes the electron distribution and catalytic reaction energy barrier, leading to ultralow hydrogen evolution reaction overpotentials at all pH conditions.